Mobile application for a web-based digital asset management system - Shafiqah Rostam (2018)
The existing Asset Management and Production System (AMPS) is a web-based system with cloud functionality for users involved in projects to collaborate with asset tracking and project management capabilities. With more users accessing web services through their mobile devices, there is a need to have AMPS readily accessible on-the-go with little to no functional limitation with the web version. This project is the third iteration of the AMPS Android application, focusing on its front-end development which aims to re-design the current application to provide better user experience, improve on the existing functionality and addition of new functions not found in the current application.